2017
DOI: 10.1063/1.4986311
|View full text |Cite
|
Sign up to set email alerts
|

High-performance ultraviolet photodetectors based on lattice-matched InAlN/AlGaN heterostructure field-effect transistors gated by transparent ITO films

Abstract: We demonstrate high-performance ultraviolet photodetectors (UV-PDs) based on lattice-matched (LM) InAlN/AlGaN heterostructure field-effect transistors (HFETs) gated by transparent ITO films. Low dark currents of 6.8 × 10−8 and 6.1 × 10−7 A/mm and high photocurrent gains over four and three orders of magnitude were obtained for the LM In0.12Al0.88N/Al0.21Ga0.79N and In0.10Al0.90N/Al0.34Ga0.66N HFETs, respectively. The negative threshold voltage shifts under illumination indicate that most of the photo-generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…19,20 High-sensitivity photodetectors based on InAlN nanophotonic structure is applicable from deep DUV to NIR region. 5,7,21 With controlling composition of InAlN with In-content B0.17, strain-less multilayer InAlN/GaN-distributed Bragg reflectors (DBRs) with high a peak reflectivity can be grown directly onto nanodevices structures for fabricating vertical-cavity surface-emitting lasers (VCSELs). 22,23 To aid the development of nanodevices based on core-shell InAlN NRs, it is crucial to have a theoretical tool to test different design scenarios and to help the interpretation of the electronic properties of as-synthesized core-shell InAlN NRs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 High-sensitivity photodetectors based on InAlN nanophotonic structure is applicable from deep DUV to NIR region. 5,7,21 With controlling composition of InAlN with In-content B0.17, strain-less multilayer InAlN/GaN-distributed Bragg reflectors (DBRs) with high a peak reflectivity can be grown directly onto nanodevices structures for fabricating vertical-cavity surface-emitting lasers (VCSELs). 22,23 To aid the development of nanodevices based on core-shell InAlN NRs, it is crucial to have a theoretical tool to test different design scenarios and to help the interpretation of the electronic properties of as-synthesized core-shell InAlN NRs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]107 Therefore, many optoelectronic devices can possibly be fabricated from InAlN alloys, which are applicable in a wide wavelength range covering deep-ultraviolet (DUV) to near infrared (NIR), such as light-emitting diodes, laser diodes, solar cells, and photodetectors. [4][5][6][7][8] However, InAlN thin film often contains large number of structural defects and compositional inhomogeneity owing to a wide-range composition immiscibility of the In x Al 1Àx N (0.1 o x o 0.9), low dissociation temperature of InN (B550), and mismatches in lattice and coefficient of thermal expansion to common substrates. [9][10][11] Alternatively, InAlN grown in the form of lowdimensional nanostructures can provide an opportunity to overcome the effects of lattice mismatch like threading dislocations formation and substrate-film strain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the conventional photodetector configurations, phototransistors (PTs) based on AlGaN/GaN HEMT structures [8] have also been presented. Three methods of gate control have been explored, including recessed barrier gate [9][10][11], Schottky gate [12][13][14], and p-GaN gate [15][16][17]. Among these approaches, PT with a p-GaN optical gate has shown excellent comprehensive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Among various electric materials, electrically conductive impurity-doped metal oxides are promising for emerging electronics because of their inherent atmospheric stability and temperature resistance. Al-doped ZnO (AZO) films have been intensively studied as conductive metal oxide electrodes because of their high electrical conductivity and visible-light transmittance as well as abundance of resources. However, it has been reported that deposited AZO nanofilms are easily dissolved in acidic or basic solutions, , limiting their utilization under harsh conditions. To overcome the chemical instability of AZO, the formation of a chemically stable capping layer (TiO 2 ) on AZO nanofilms has been proposed .…”
Section: Introductionmentioning
confidence: 99%